2020
DOI: 10.23736/s0022-4707.20.10412-2
|View full text |Cite
|
Sign up to set email alerts
|

A 12-month continuous and intermittent high-impact exercise intervention and its effects on bone mineral density in early postmenopausal women: a feasibility randomized controlled trial

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
14
0
2
Order By: Relevance
“…The results of this study showed that square dance was correlated with high BMD density of lumbar spine and total hip except femoral neck. Square dance is a relatively low-impact exercise with small size of joint movement and does not apply much bending force to femoral neck, which is different from those high-impact exercises such as running or jumping (21). Higher low limb muscle strength and longer single-stance time were detected in subjects of square dance group, which suggested that square dance was associated with better muscle function and body balance.…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study showed that square dance was correlated with high BMD density of lumbar spine and total hip except femoral neck. Square dance is a relatively low-impact exercise with small size of joint movement and does not apply much bending force to femoral neck, which is different from those high-impact exercises such as running or jumping (21). Higher low limb muscle strength and longer single-stance time were detected in subjects of square dance group, which suggested that square dance was associated with better muscle function and body balance.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies found lower BMD in elite ballet dancer [ 23 , 24 ], which seems contrary to our results. But we think square dance is a relatively low-impact exercise with small size of joint movement and does not apply much bending force to femoral neck, which is different from those high-impact exercises such as running or jumping [ 25 ], which are common movements in ballet. Higher lower limb muscle strength and longer single-stance time were detected in subjects of square dance group, which suggested that square dance was associated with better muscle function and body balance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed maintenance or lower decreases in BMD compared to control groups [ 17 , 22 , 24 , 25 ], and some concluded that no changes were seen in BMD following the intervention [ 18 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…High-impact resistance training with jumping sequences is shown to positively impact the bone due to their high strain properties, leading to increased muscular demand and a positive osteogenic effect on the recruited bony segments [ 17 ]. Engelke et al’s study demonstrated the impact of a three-year program of integrated endurance, jumping, and high-intensity resistance training on BMD.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation